2021
DOI: 10.1016/j.ophtha.2020.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Ophthalmic Hospital-Based Virtual Service during the COVID-19 Pandemic

Abstract: The management of ophthalmic diseases in the virtual hospital can be implemented and is complementary to those of on-site F2F clinics. Virtual clinical service may be a useful model in the post-COVID-19 pandemic “new normal”.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 7 publications
(8 reference statements)
2
33
0
Order By: Relevance
“…48 This model has been used by eye care providers to scale up responses and reduce unnecessary encounters during COVID-19, such as the virtual internet hospital model applied by the Zhongshan Ophthalmic Centre in China. 49 In addition to ophthalmology, various AI-based conversational chatbots have been applied with this model in pilot studies, 63 although more robust clinical validation is required. 64,65 Conversely, the hub-and-spoke model augments clinical services in geographically remote settings (the so-called spoke) through patient-provider or provider-provider consultations with providers or specialists based in referral centres or tertiary hospitals serving the catchment area (the so-called hub).…”
Section: Out-of-hospital Operational Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…48 This model has been used by eye care providers to scale up responses and reduce unnecessary encounters during COVID-19, such as the virtual internet hospital model applied by the Zhongshan Ophthalmic Centre in China. 49 In addition to ophthalmology, various AI-based conversational chatbots have been applied with this model in pilot studies, 63 although more robust clinical validation is required. 64,65 Conversely, the hub-and-spoke model augments clinical services in geographically remote settings (the so-called spoke) through patient-provider or provider-provider consultations with providers or specialists based in referral centres or tertiary hospitals serving the catchment area (the so-called hub).…”
Section: Out-of-hospital Operational Modelsmentioning
confidence: 99%
“…Issues from interactions with the existing models of care (either to overlay, augment, replace current models, etc) Ethics and medicolegal constraints Provider acceptance (eg, clinicians, nurses) 54 Pilot validation studies (with a focus on clinical outcomes or performance) 49,55 Guidelines for use, liability for negative outcomes, safety net mechanisms 61,66 Mesosystem (eg, hospital, hub-and-spoke model)…”
Section: Potential Barriersmentioning
confidence: 99%
“…Firstly, non-COVID-19 patients' medical needs have been greatly affected, which may have caused psychological distress. However, the emergence of a virtual hospital, not limited by place or time that enabled patients to see physicians while avoiding a crowded waiting room, became an alternative for many patients ( 7 ). Online consultation can address some patients' needs, but it is uncertain whether seeing a health care provider virtually can affect patients' mental state.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the findings of a study on this program demonstrated that the development of a virtual hospital could be an effective strategy to enhance the capacity of hospitals following the rapid spread of COVID-19 (7). Another survey in China showed that using virtual hospitals to deliver ophthalmic services during COVID-19 was very effective and could continue even after the pandemic (9). Providing virtual care can facilitate social distancing measures and decrease patient wait time.…”
mentioning
confidence: 99%